Scar Healing after Breast Reconstruction: A 5-year Follow-up in Asian Patients - Risa Murakami; Tomohiro Shiraishi; Mikiko Imamura; Akihiko Takushima; Hirotaka Suga (Journal of Plastic and Reconstructive Surgery)
Objectives: Hypervascularity, hypertrophy, and hyperpigmentation of breast scars often persist for several years after reconstruction. There are few reports on the long-term follow-up of postoperative scars after breast reconstruction. We previously reported that at 1 year after reconstruction, >30% of Asian patients showed abnormal scars. In this study, we followed these patients for as long as 5 years postoperatively. Methods: We followed 101 Asian patients who underwent immediate two-stage implant-based breast reconstructions between 2013 and 2017 and still had abnormal scars involving hypervascularity, hypertrophy, or hyperpigmentation at 1 year postoperatively. We conducted annual follow-up for an additional 4 years, assessing the time until improvement and performing statistical analysis of factors related to the persistence and healing of abnormal scars. Results: Hypervascularity improved in 12%, 37%, 68%, and 82% of patients at 2, 3, 4, and 5 years, respectively. Most cases improved between 3 and 4 years postoperatively. Among the patients with both hypervascularity and hypertrophy at 1 year, 36% had residual hypervascularity at 5 years compared with 9.8% of those with hypervascularity only at 1 year. Hypertrophy improved within 5 years in 56% of the cases. Hyperpigmentation improved within 5 years in only 21% of the cases. There was no significant association between abnormal scars and age or body mass index. Conclusions: Even in Asian patients with persistent hypervascularity of breast scars, most cases improve within 5 years after reconstruction. However, hypervascularity tends to persist in cases that also show hypertrophy. Compared with hypervascularity and hypertrophy, hyperpigmentation showed worse 5-year improvement.